Scientific, Educational and Philosophical Views of Aziziddin Nasafi - Qudratovna, Marhabo Kazakova (International Journal of Psychosocial Rehabilitation, 2020)
Studying the life and activities of scholars who have made a significant contribution to the development of the world culture, working in different fields of science, and getting acquainted with the scientific works created by them will further enrich the existing knowledge of world history, culture and universal values. In turn, one of the most important tasks is to study the views of the great thinkers who have made a significant contribution to the development of national and international culture. The article analyzes the possibilities of introducing the scientific heritage of the world-famous philosopher Aziziddin Nasafi, who was born in ancient origin and known for his rich spiritual heritage. Nafafi’s philosophical views are aimed at educating the ideal person, and the role and importance of these views in the pedagogical process are reflected in this article.